Bridging the gap: The role of artificial intelligence in enhancing Arabic language learning, translation, and speech recognition - Al-Shaboul, Ibrahim Abdallah; Ali, Abdirahman Abdi; Kariem, Aa-ieshah Abrahams; Zarovna, Inna; Glushchenko, Tatiana; Khasawneh, Mohamad Ahmad Saleem (Research Journal in Advanced Humanities, 2025)
This study explores the transformative impact of Artificial Intelligence (AI) on Arabic language learning, translation, and speech recognition, addressing both the potential and challenges of these technologies. Through a mixed-methods approach, including surveys, focus groups, and interviews with 51 participants from Lebanon and Saudi Arabia, the research examines the effectiveness of AI tools in enhancing Arabic language proficiency, the challenges posed by dialectal variations and cultural nuances, and the need for greater cultural sensitivity in AI development. The findings reveal that while AI tools are effective for basic tasks such as vocabulary building and pronunciation feedback, they struggle with complex language structures, regional dialects, and culturally specific expressions. The study highlights the importance of developing more advanced, inclusive, and culturally sensitive AI models to better meet the needs of Arabic speakers. By addressing these challenges, AI has the potential to revolutionize Arabic language processing, fostering cross-cultural communication and preserving linguistic diversity in an increasingly globalized world.